DIDACTIC SUPPORT OF THE ORGANIZATION OF INDEPENDENT EDUCATIONAL ACTIVITY OF MASTERS OF SOCIAL PEDAGOGY (Pedagogy of Higher and Secondary Education, 2022)
The article substantiates didactic foundations achieve high efficiency of the organization self-leaming activity Masters of Social Pedagogy. Developed by the content self-training economic operators, altocated diagnostic materials. Advocated the need for optimal connection of independent activities with vocational and practical tasks, targeted on the formation and devebpment of professfonal thinking of foture social workers.
Keywords: independent foaming activities; social pedagogue; vocational and practical assignments